Proceedings of the Evaluation and Assessment in Software Engineering 2020
DOI: 10.1145/3383219.3383220
|View full text |Cite
|
Sign up to set email alerts
|

A Multiple Case Study of Artificial Intelligent System Development in Industry

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The process of Requirements Engineering for AI-based systems (RE4AI) is different from traditional systems [Kostova et al 2020], and there is an additional complexity to the development of AI-based systems [Nguyen-Duc et al 2020], because there is a dependency between the large amount of data and algorithms [Belani et al 2019], being observed in some cases the use and extension of already well-established approaches, principles and tools in Software Engineering for the development of AI-based systems [Schleier-Smith 2015]. Some authors have explored the challenges of Requirements Engineering, as well as Software Engineering, for AIbased systems (e.g., [Belani et al 2019] [Nguyen-Duc et al 2020] [Schleier-Smith 2015] [Lwakatare et al 2019). Thus, in the context of AI-based systems there is a difficulty in tracing the output of a model back to system requirements, as they may not be explicitly documented, and possible issues arise only when the system is deployed [Raji et al 2020].…”
Section: Requirements Engineering For Aimentioning
confidence: 99%
“…The process of Requirements Engineering for AI-based systems (RE4AI) is different from traditional systems [Kostova et al 2020], and there is an additional complexity to the development of AI-based systems [Nguyen-Duc et al 2020], because there is a dependency between the large amount of data and algorithms [Belani et al 2019], being observed in some cases the use and extension of already well-established approaches, principles and tools in Software Engineering for the development of AI-based systems [Schleier-Smith 2015]. Some authors have explored the challenges of Requirements Engineering, as well as Software Engineering, for AIbased systems (e.g., [Belani et al 2019] [Nguyen-Duc et al 2020] [Schleier-Smith 2015] [Lwakatare et al 2019). Thus, in the context of AI-based systems there is a difficulty in tracing the output of a model back to system requirements, as they may not be explicitly documented, and possible issues arise only when the system is deployed [Raji et al 2020].…”
Section: Requirements Engineering For Aimentioning
confidence: 99%
“…Designing ML systems: Components with ML capabilities are becoming an architectural part of software systems, sharing cross-cutting functional and non-functional concerns [179]. Monitoring for potential performance degradation on production [P56][P60] and high-volume data processing [P12][P56] are two important design considerations for ML systems.…”
Section: Potential Research Directions From the Se Perspectivementioning
confidence: 99%
“…It may be useful to use different ML problems, such as clustering, to find further challenges. Some of the concerns, such as some non-functional requirements, may be domain-specific [179] and can be discovered by exploring various ML problems.…”
Section: Use Of Various ML Problemsmentioning
confidence: 99%
“…al. [16] summarize the engineering challenges for developing and operating AI systems into seven categories: requirements, data management, model design and implementation, model configuration, model testing, evaluation and deployment, and processes and practice. Kästner et.…”
Section: Challenges Of Developing and Operating Ai-based Asmentioning
confidence: 99%